Mineralogy and geochemistry of shale from Shanxi Formation, Southern North China Basin: Implication for organic matter accumulation - Qian Chen; Pei Li; Xiaoliang Wei; Changsheng Chen; Wei Dang; Haikuan Nie; Jinchuan Zhang (Unconventional Resources)
The Permian Taiyuan and Shanxi coal-bearing formations are recognized as the primary source rocks and promising shale gas reservoirs in North China. Based on lithologic observations, mineral and major elemental analyses of the Shanxi Sahle in the Southern North China Basin (SNCB), we conducted a preliminary investigation into the depositional environment, climate, and factors controlling the organic matter (OM) accumulation. The main findings are as follows: (1) The Shanxi Formation results from a transition in depositional environment, shifting from tidal flats to delta plains. The Shanxi Shale is primarily composed of clay minerals (34.24 %–75.20 %) and quartz (23.80%–46.39 %), with a notably low carbonate content (<5 %). (2) Illite in the lower sections of the Shanxi Shale is likely sourced from detrital input rather than chemical conversion, while the dissolution of potassium feldspar may account for the elevated kaolinite content. This is further supported by the oxygen level variations between the lower and upper shale intervals. Moreover, no significant positive correlation was observed between SiO2 and Al/Na ratios, nor between clay minerals and total organic carbon (TOC) content. This suggests that the intensity of OM modification prior to diagenesis plays a pivotal role in OM accumulation, aligning with the positive correlation between inertinite proportion and TOC content. (3) Organic matter inputs from fluvial systems were likely influenced by upstream mire conditions, where precursor peat may have accumulated. Unlike marine shale, the intensity of weathering, which varies with climate and transportation distance, is considered to have significantly impacted both the maceral composition and OM richness in the tide-delta deposited Shanxi Shale.